(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to solving the psychological problems of formation of the readiness of future social workers to certain peculiarities of professional activity, namely, the formation of the ability to act in stressful situations, which are often encountered by professionals working in the field of social work. The stress state is considered as causing a special psychic state, which is a peculiar form of reflection the subject of a complex, extreme situation in which it is located. Emphasizes the need for the formation and development of stress resistance, which in turn consists of four components: cognitive, communicative, emotional and motivational. Understanding stress is considered as the overall quality of the personality, characterized by the ability to withstand stress factors for the period of time that is necessary for the organization of new conditions, in which this stressor will not be a threat. With regard to the stress resistance of a social worker, it is defined as the ability to demonstrate adequate behaviour in stressful situations related to professional activity; Be able to regulate their own emotional state in such a way as to maintain a mental balance for the sake of effective professional activity as well as general life and health; the ability to make the right decisions in crisis and critical situations; the ability to maintain tolerance, tolerance and persistence for a long time in the pursuit of success in solving professional problems. For this purpose, a program for the formation of stress susceptibility in the professional activities of future social workers has been developed, containing both theoretical and practical sections that will be included in the academic discipline "Social Work with Victims of Emergencies and Migrants". It is noted that ability to adequately behave in difficult situations in professional activity demonstrates not only his endurance and tolerance, which should testify to the professionalism of a social worker, but also prevents his professional deformation and promotes the preservation of health. The program of formation and development of resilience of future social workers is proposed. Operation of this program is planned within the framework of discipline "Social work with victims of emergencies and migrants", which is obligatory for education at the level of education "bachelor" specialty "Social work".